Pengaruh Penggunaan Bahasa Jawa Metode IMMANN terhadap karakter Siswa Sekolah Menengah Atas Negeri 7 Yogyakarta - Heri Kurnia; Ika Rahayu Trisnawati; Mas Fierna Janvierna Lusie Putri (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The existence of modernization in the development of this era has changed the language order used by the community, especially young people. The preservation of regional languages (Javanese) to young people has decreased due to several factors, namely association in making friends, there is no balance in using regional languages and national languages both in the home and school environment. This can be a shift in the use of the Javanese language. The purpose of this study is to find out how much influence the use of the Javanese IMMANN method has on students' character education. This research is a quantitative descriptive research. In this study, the population of all students of SMA Negeri 7 Yogyakarta was used. The researcher's sampling technique uses a simple random sampling technique. The use of a sample of 247 students from a large population of 853 students. The research was conducted at SMA Negeri 7 Yogyakarta from March to April 2023. In data processing, the researcher used the help of the SPSS version 23 program. Statistical analysis produces a regression equation Y = 4.449 + 1.002X, meaning that if the value of using Javanese language IMMANN method (X) increases by 1 unit, the value of character education (Y) will increase by 1.002 units with a constant value of 4.449. Hypothesis testing shows that independent variables are proven to significantly affect dependent variables. The coefficient of determination (R Square) of 0.550 means that the independent variable affects the bound variable by 55% and the remaining 45% is influenced by other variables that are not included in this study.